HUMAN MORALS IN THE RETROSPECTIVE OF COGNITIVEANTHROPOLOGICAL ANALYSIS - Horielova, Veronika (Актуальні проблеми правознавства, 2021)
The article is devoted to the problem of morality, from ancient times to the present. An analysis of historical approaches to understanding morality. It is proved that important in the modern transformation of the conceptual foundations of morality is the man himself, whose cognitive behavior in all ages is based on historical, legal and religious programs, which unite and organize it. Relevant strategies of such programs reflect their separate, inherent only in them, cognitive representations, which not only reflect moral ideas about reality, but also are able to create a «new reality», distorting the old. Emphasis is placed on the need to consider this problem, due to the need to establish a causal relationship between morality and law.